2005
DOI: 10.1103/physrevlett.94.036601
|View full text |Cite
|
Sign up to set email alerts
|

Organic Homojunction Diodes with a High Built-in Potential: Interpretation of the Current-Voltage Characteristics by a Generalized Einstein Relation

Abstract: We realize p- and n-type doping of the organic semiconductor zinc-phthalocyanine using a novel strong organic donor. This allows us to demonstrate the first stable and reproducible organic p-n homojunctions. The diodes show very high built-in potentials, attractive, e.g., for organic solar cells. However, the diode characteristics cannot be described by the standard Shockley theory of the p-n junction since the ideality factor strongly increases with decreasing temperature. We show that this behavior can be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
119
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 25 publications
13
119
2
Order By: Relevance
“…The breakthrough properties of such devices have only been rarely investigated, see, for example, ref 15. The advantage of the pin-diode concept 16 is that the geometry and the potentials within the semiconductor layers can be controlled very precisely, thus allowing the study of the tunneling effects, which sensitively depend on minute variations of these parameters, in a very controlled manner. Thus, the tunneling current is independently tunable by two parameters: the thickness of the intrinsic interlayer (IIL) and the doping concentration of the electron and hole transport layers (ETL/ HTL).…”
mentioning
confidence: 99%
“…The breakthrough properties of such devices have only been rarely investigated, see, for example, ref 15. The advantage of the pin-diode concept 16 is that the geometry and the potentials within the semiconductor layers can be controlled very precisely, thus allowing the study of the tunneling effects, which sensitively depend on minute variations of these parameters, in a very controlled manner. Thus, the tunneling current is independently tunable by two parameters: the thickness of the intrinsic interlayer (IIL) and the doping concentration of the electron and hole transport layers (ETL/ HTL).…”
mentioning
confidence: 99%
“…13 For our next study, we chose metal-free phthalocyanine (H 2 Pc) which is regarded as being p-type, with no reports of it being n-type. A few exceptions are n-type metal phthalocyanine doped with complexes having central metals like ruthenium, 10,14 although there have been intensive studies on doping 15,16 such as F 4 -TCNQ acting as typical p-type dopants. 17 In this study, we used molybdenum oxide (MoO 3 ) 12,13,18,19 and cesium carbonate (Cs 2 CO 3 ) 20,21 as acceptor and donor dopants, respectively.…”
mentioning
confidence: 99%
“…These results strongly suggest that, in principle, almost all single organic semiconductors can be controlled to both n-type and p-type by doping alone, similar to the case of inorganic semiconductors. For the cases of C 60 , H 2 Pc, ZnPc, pentacene, and CBP, pn-homojunctions were formed [34,36,38,44,46]. …”
Section: Generalitymentioning
confidence: 99%
“…[32,33] were found. In terms of donors that are relatively stable in air, Harada et al found a Ru-complex and applied it to fabricate pn-homojunctions in zinc phthalocyanine [34,35] and pentacene [36]. Recently, compounds of alkaline metals, such as Cs 2 CO 3 [37,38], and Co-complexes [39] acting as donor dopants have been identified.…”
Section: Introductionmentioning
confidence: 99%